La dactilopintura en el desarrollo cognitivo en los niños de 3 a 4 años de la unidad educativa “Roberto Alfredo Arregui Chauvin”, del cantón Guaranda, provincia de Bolívar, periodo 2024 - Benavides Aguay, Grace Estefany (2025)
It is essential to recognize the relevance of fingerprinting in the first years of life, since it constitutes the basis for the education and training of children, strengthening their cognitive development in various areas, allowing them to function adequately in their daily activities. It is also a common practice in early education, giving them the opportunity to explore color and texture in a direct, sensory way. The objective of this research was to demonstrate the effectiveness of fingerprinting in enriching the cognitive development of children aged 3 to 4 years at the Roberto Alfredo Arregui Chauvin Educational Unit, located in the city of Guaranda. To achieve this objective, a study was carried out with a group of 12 children from initial lleve II, using direct observation as the main method. In addition, fingerprinting activities were carried out, in which the students participated both individually and in groups. Our project's approach is qualitative, allowing us to collect data. We used an observation sheet to evaluate the children's performance, yielding both positive and negative results. A teacher survey was also conducted, focusing on aspects related to our research. Finally, the results were analyzed and interpreted, thereby achieving the research objectives.